Jawabanmu

2014-03-27T08:07:13+07:00
X1 + X2 =  \frac{3}{2}
x1.x2 =  \frac{4}{2} = 2

(x1 + 2) + (x2 + 2) = (x1 + x2) + 4 = (  \frac{3}{2} + 4 =  \frac{11}{2}  )
(x1 + 2).(x2 + 2) = x1.x2 + 2(x1 + x2) + 4 = 2 +  \frac{3}{2} + 4 = \frac{15}{2}

persamaan yang baru:
x² - {(x1 + 2) + (x2 + 2)}x + (x1 + 2).(x2 + 2) = 0 
x² -  \frac{11}{2}x + \frac{15 }{2}  = 0 
2x² - 11x + 15 = 0
2014-03-27T08:16:52+07:00
2x*-3x+4=0 (2x-2)(x-2)=0 x1=1 x2 =2 kuadran baru 2X*+((x1+2)+(x2+3))X + ((x1+2)(x2+2)) 2X*+((1+2)+(2+2)) X + ((1+2)(2+2)) 2X*+7X+12 ma'af... sulit ngetik kyk gini di hp